Preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres

By adopting a dual modification design of carbon-coated and molybdenum-doped vanadium oxide microspheres in vanadium-based materials, carbon-coated molybdenum-doped vanadium-oxide microspheres were prepared, which solved the problems of easy dissolution and poor conductivity of vanadium-based materials, and significantly improved its electrochemical performance and cyclic stability.

CN119650620APending Publication Date: 2025-03-18XUZHOU COLLEGE OF INDAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411668926.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Vanadium-based materials are easily dissolved and have poor conductivity, resulting in poor cycle stability and slower electrochemical kinetics, thus limiting their large-scale application.

Method used

Carbon-coated molybdenum-doped vanadium oxide microspheres were prepared by a dual modification design strategy of carbon coating and molybdenum doping.

Benefits of technology

It significantly improves the electrochemical performance of vanadium trioxide cathode material, improves specific capacity and cycle stability, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650620A_ABST
    Figure CN119650620A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres, and relates to the technical field of positive electrode materials of zinc ion batteries. The preparation method of the carbon-coated molybdenum-doped vanadium oxide microspheres comprises the following steps: dissolving a vanadium source and a molybdenum source in a certain proportion in a mixed solution of isopropanol and glycerol, and carrying out solvothermal reaction; and carrying out centrifugal washing on the reaction product, drying, and calcining in a tubular furnace to finally obtain the carbon-coated molybdenum-doped vanadium oxide microspheres. The carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material is prepared by combining a simple one-step solvothermal method with subsequent heat treatment, the preparation process is simple, and the problems that a vanadium-based positive electrode material of an aqueous zinc ion battery is easy to dissolve and poor in conductivity and cycling stability are well solved by adopting a dual-modification strategy. The carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material prepared by the invention has high tap density, reversible specific capacity and good cycling stability and rate capability, and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc ion battery positive electrode materials, and in particular to a preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres. Background Art

[0002] As people's demand for new energy storage devices with high capacity, long cycle life, portability and low price becomes more and more urgent, aqueous zinc-ion batteries are favored by people due to their low production cost, safety and reliability, high specific capacity and other advantages. Vanadium-based materials are rich in reserves, low in development and utilization cost, and have an open layer or tunnel-like structure, which is conducive to Zn 2+ The advantages of embedding / de-embedding and high capacity characteristics make it an ideal positive electrode material for AZIBs. Vanadium has a rich valence state, with common valence states ranging from +2 to +5. It can undergo redox reactions with multiple electron transfers and show high capacity characteristics. In addition, vanadium-based compounds have different crystal structures and electrochemical properties. Common vanadium-based compounds include vanadium-based oxides, vanadium-based phosphates, and vanadium-based sulfides. Most of them have open structures such as open layers or tunnels, which are beneficial to the embedding / de-embedding of ions, and are therefore mostly used in battery electrode materials. However, vanadium-based materials are easily soluble and have poor conductivity, resulting in poor cycle stability and slow electrochemical kinetics, which limits their large-scale application.

[0003] Therefore, it is urgent to rationally modify vanadium-based materials to improve the poor conductivity, easy dissolution and unstable structure of vanadium-based materials and further improve the electrochemical performance. In recent years, researchers have used methods to modify vanadium-based materials, including defect engineering, micromorphology control, intercalation engineering, structural composites, etc. The electrochemical properties of vanadium-based materials can be improved by the above modification methods, but to date, there are few reports on the effects of dual modification of coating and doping on the performance of vanadium-based positive electrode materials. In addition, how to use simpler and more effective modification methods to prepare vanadium-based positive electrode materials for zinc-ion batteries with excellent performance still needs to be explored. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing and applying carbon-coated molybdenum-doped vanadium oxide microspheres, which solves the problem that vanadium-based materials are easily soluble and have poor conductivity, resulting in poor cycle stability and slow electrochemical kinetics, thereby limiting their large-scale application.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres comprises the following steps:

[0009] S1. Dissolve the vanadium source and the molybdenum source in an organic solvent and stir thoroughly;

[0010] S2. The mixed solution obtained in S1 is transferred to a reactor for solvothermal reaction;

[0011] S3. The product obtained in S2 is centrifuged, washed and dried;

[0012] S4. The precursor powder obtained in S3 is heat treated to obtain a final product;

[0013] Through the above technical scheme, the dual-modification design strategy for preparing carbon-coated molybdenum-doped vanadium oxide microspheres by a one-step solvothermal method provided by the present invention can significantly improve the electrochemical performance of vanadium trioxide positive electrode materials. The test results show that the specific capacity of the zinc ion battery assembled with carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode materials provided by the first aspect of the present invention after 250 cycles is 272.4 mAh g -1 , which is significantly higher than the specific capacity of zinc-ion batteries assembled with vanadium oxide microsphere positive electrode materials without molybdenum doping.

[0014] Furthermore, the molar ratio of Mo and V in the S1 is (0-15):100, the molar ratio is (2-8):100, and in specific examples, the molar ratio of Mo:V is 0:100, or 2:100, or 4:100, or 6:100, or 8:100.

[0015] Further, the molybdenum source in S1 includes one or more of ammonium molybdate, calcium molybdate, and sodium molybdate, the vanadium source in S1 includes one or more of ammonium metavanadate, vanadium trichloride, and magnesium vanadate, and the organic solvent in S1 includes one or more of isopropanol, glycerol, ethylene glycol, and glycerol;

[0016] Through the above technical scheme, the solvothermal method used in S2 is used to prepare vanadium trioxide. The process is simple and the synthesis temperature is low. The reaction can be effectively controlled by changing the reaction conditions.

[0017] Furthermore, the solvent thermal reaction time in S2 is 3 to 24 hours, the optimal reaction time is 12 hours to 16 hours, and the reaction temperature is 120 to 200°C;

[0018] Through the above technical solution, the optimal reaction temperature for preparing the material by the solvent thermal method in a specific example is 150-180°C.

[0019] Furthermore, during the centrifugal treatment of S3, deionized water and ethanol are used alternately for centrifugal treatment, and the centrifugal speed is 4000-8000 r min -1 .

[0020] Furthermore, in S3, the drying time is 12 hours and the drying temperature is 80°C.

[0021] Furthermore, the heat treatment method in S4 is calcination in a tube furnace, the calcination temperature is 300-700°C, the optimal calcination temperature is 500°C, the calcination time is 1-8h, and the optimal calcination time is 3h. The calcination atmosphere is nitrogen or argon, and the heating rate is 4°C min -1 .

[0022] Furthermore, the carbon-coated molybdenum-doped vanadium oxide microsphere electrode material prepared by any of the preparation methods described above.

[0023] Furthermore, the carbon-coated molybdenum-doped vanadium oxide microsphere electrode material is used as a positive electrode material for zinc ion batteries.

[0024] Furthermore, a positive electrode for a zinc ion battery is provided, wherein the positive electrode for the zinc ion battery comprises a conductive agent, a binder and the carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material

[0025] Furthermore, a zinc ion battery is provided, the zinc ion battery comprising the zinc ion battery negative electrode, positive electrode, a separator disposed between the positive and negative electrodes, and an electrolyte

[0026] (III) Beneficial effects

[0027] The present invention provides a preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres, which have the following beneficial effects:

[0028] 1. The present invention provides a preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres. The electrochemical performance of the prepared vanadium oxide microsphere positive electrode material is significantly improved through the dual modification design strategy of carbon coating and molybdenum doping. The dual modification design strategy is selected mainly based on the following considerations: on the one hand, carbon coating can effectively improve the conductivity of the material, and the carbon coating layer has a good protective effect on the vanadium-based main body, which can not only inhibit the agglomeration of nanoparticles, but also effectively prevent the dissolution of the vanadium-based main material, thereby improving its cycle stability. On the other hand, metal element doping can effectively improve the conductivity and cycle stability of the material, and the ionic radius of molybdenum ions and vanadium ions is similar, and appropriate doping will not cause changes in the structure of the vanadium-based main material. At the same time, the prepared microspheres have a large tap density, which is beneficial to improving their volume energy density. Therefore, the modification research on vanadium-based positive electrode materials through the dual modification strategy of carbon coating and molybdenum doping has important practical significance, and provides valuable experience for effectively improving the electrochemical performance of AZIBs vanadium-based positive electrode materials.

[0029] 2. The present invention provides a preparation method and application of carbon-coated molybdenum-doped vanadium oxide microspheres. The preparation method is simple to operate and efficient, and can synthesize high-quality products in a relatively short time. In addition, the above-mentioned carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material effectively improves the conductivity and cycle stability of vanadium-based positive electrode materials. The present invention has a wide range of research on metal doping, regulation of microspheres and preparation methods, and can provide reference and reference for related research in other fields.

[0030] 3. The present invention provides a method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres and their application. The present invention uses a simple one-step solvothermal method combined with subsequent heat treatment to prepare carbon-coated molybdenum-doped vanadium oxide microspheres as positive electrode materials. The preparation process is simple, and the double modification strategy adopted has effectively solved the problems of easy solubility, poor conductivity and cycle stability of vanadium-based positive electrode materials in aqueous zinc ion batteries. The carbon-coated molybdenum-doped vanadium oxide microspheres as positive electrode materials prepared by the present invention have high tap density, reversible specific capacity, good cycle stability and rate performance, and have good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an X-ray diffraction pattern of carbon-coated molybdenum-doped vanadium oxide microspheres prepared in Example 2 of the present invention;

[0032] Figure 2 This is a transmission electron microscopy image of carbon-coated molybdenum-doped vanadium oxide microspheres prepared in Example 3 of the present invention;

[0033] Figure 3 Schematic diagram of the rate performance of the carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material at different current densities prepared in Example 5 of the present invention;

[0034] Figure 4 The undoped sample prepared in Example 1 of the present invention and the doped sample prepared in Example 5 were -1 Comparison curve of long-term cycling performance under different current densities. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Embodiment 1:

[0037] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and dissolve it in a mixed solution of isopropanol and glycerol without adding ammonium molybdate, that is, the Mo:V molar ratio is 0:100. After magnetic stirring for 2 hours, transfer it to a reactor and keep it at 180°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate of increase is 4°C min -1 After cooling, the final undoped powder sample was obtained.

[0038] Embodiment 2:

[0039] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 35.3 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 2:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 150°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate is 4°C min -1 , and the final product is obtained after cooling.

[0040] Embodiment 3:

[0041] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 35.3 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 2:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 180°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate is 4°C min -1 , and the final product is obtained after cooling.

[0042] Embodiment 4:

[0043] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 70.6 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 4:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 150°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate is 4°C min -1 , and the final product is obtained after cooling.

[0044] Embodiment 5:

[0045] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 70.6 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 4:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 180°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate is 4°C min -1 , and the final product is obtained after cooling.

[0046] Embodiment 6:

[0047] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 105.9 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 6:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 150°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate is 4°C min -1 , and the final product is obtained after cooling.

[0048] Embodiment 7:

[0049] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 105.9 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 6:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 180°C for 12 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate of increase is 4°C min -1 , and the final product is obtained after cooling.

[0050] Embodiment 8:

[0051] Use a balance to weigh 1170 mg of ammonium metavanadate as a vanadium source and 141.3 mg of ammonium molybdate as a molybdenum source, and dissolve them together in a mixed solution of isopropanol and glycerol, where the Mo:V molar ratio is 8:100. After magnetic stirring for 2 hours, transfer to a reactor and keep it at 180°C for 16 hours. The cooled solution is centrifuged and washed alternately with deionized water and ethanol, and the precipitate after centrifugation is vacuum dried at 80°C for 12 hours. The dried product is placed in an alumina porcelain boat and calcined in a tubular furnace under a nitrogen atmosphere for 3 hours. The calcination temperature is 500°C and the rate of increase is 4°C min -1 , and the final product is obtained after cooling.

[0052] Experimental data analysis:

[0053] Pole piece preparation: The prepared carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material is sieved and weighed with acetylene black and 6wt% PVDF solution in a mass ratio of 7:2:1, and an appropriate amount of NMP is added as a mixing aid to adjust the product to an appropriate consistency. After that, it is magnetically stirred for 4 hours to obtain a uniform slurry. The slurry is evenly coated on a titanium foil, which is then placed in a vacuum drying oven and vacuum dried at 120°C for 12 hours. The dried titanium foil is cut into 10 mm circular pole pieces with a manual puncher, and the mass of the pole pieces is weighed and recorded.

[0054] Battery assembly: The materials required to assemble aqueous zinc-ion batteries include CR2032 battery case, zinc sheet, diaphragm, electrode, gasket, spring and 2mol L -1 The trifluoromethanesulfonate aqueous electrolyte of zinc was assembled in the order of battery shell, negative electrode shell, zinc sheet, diaphragm, electrolyte, positive electrode sheet, gasket, shrapnel and positive electrode shell. After assembly, it was sealed with a button battery sealing machine and the electrochemical performance test was carried out after standing for 12 hours.

[0055] See attached Figure 1 , Figure 1This is the XRD spectrum of the carbon-coated molybdenum-doped vanadium oxide microsphere material prepared in Example 2. It can be seen that the carbon-coated molybdenum-doped vanadium oxide powder sample prepared in this example has good crystallinity, and the diffraction peak corresponds to the standard card of V2O3 (PDF#34-0187), and no other phases are found, indicating that molybdenum doping does not cause structural changes in V2O3. This shows that the technical solution can simply and effectively prepare pure carbon-coated molybdenum-doped vanadium oxide material.

[0056] See attached Figure 2 , Figure 2 This is a TEM image of the carbon-coated molybdenum-doped vanadium oxide microspheres prepared in Example 3. It can be seen from the figure that the product prepared in this example has a uniform morphology of microspheres with a diameter of about 1 to 2 microns.

[0057] See attached Figure 3 , Figure 3 The figure shows the rate performance of the carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material prepared in Example 5 at different current densities. It can be seen from the figure that the aqueous zinc ion battery assembled with the double-modified vanadium oxide microsphere positive electrode material prepared in this example has a rate performance of 0.1, 0.2, 0.5, 1.0 and 2.0A g -1 The average specific capacities at different current densities are 375.3, 298.9, 258.8, 239.7, and 219.7 mAh g -1 , at 4A g -1 The average specific capacity at high current density is still 193.9 mAh g -1 This shows that the dual modification strategy proposed in this technical solution can give vanadium oxide excellent rate performance.

[0058] See attached Figure 4 , Figure 4 The undoped sample prepared in Example 1 and the doped sample prepared in Example 5 were -1 Long cycle performance under current density. It can be seen from the figure that the doped sample exhibits excellent high-time long cycle performance. -1 The specific capacity after 250 cycles is 272.4 mAh g -1 The capacity retention rate is 81.8%, while the specific capacity of the undoped sample after 250 cycles is 195.8 mAh g -1 , the capacity retention rate is 69.8%. Therefore, the doped sample exhibits better high-time long cycle performance. The above results show that doping with an appropriate amount of molybdenum element can significantly improve the cycle stability of vanadium oxide microsphere positive electrode materials.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres, characterized in that: The following steps are involved: S1. Dissolve the vanadium source and the molybdenum source in an organic solvent and stir thoroughly; S2. The mixed solution obtained in S1 is transferred to a reactor for solvothermal reaction; S3. The product obtained in S2 is centrifuged, washed and dried; S4. Heat-treating the precursor powder obtained in S3 to obtain the final product.

2. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: The molar ratio of Mo to V in the S1 is (0-15):100, and the molar ratio is (2-8):

100.

3. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: The molybdenum source in S1 includes one or more of ammonium molybdate, calcium molybdate, and sodium molybdate; the vanadium source in S1 includes one or more of ammonium metavanadate, vanadium trichloride, and magnesium vanadate; and the organic solvent in S1 includes one or more of isopropanol, propylene glycol, ethylene glycol, and glycerol.

4. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: The solvent thermal reaction time in S2 is 3 to 24 hours, and the reaction temperature is 120 to 200°C.

5. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: During the centrifugal treatment of S3, deionized water and ethanol are used alternately for centrifugal treatment.

6. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: The drying time in S3 is 12 hours and the drying temperature is 80°C.

7. The method for preparing carbon-coated molybdenum-doped vanadium oxide microspheres according to claim 1, characterized in that: The heat treatment method in S4 is calcination in a tubular furnace, the calcination atmosphere is nitrogen or argon, the calcination temperature is 500° C., and the calcination time is 3 hours.

8. The carbon-coated molybdenum-doped vanadium oxide microsphere electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carbon-coated molybdenum-doped vanadium oxide microsphere electrode material as claimed in claim 8 as a positive electrode material for zinc ion batteries.

10. A zinc ion battery positive electrode, characterized in that: The positive electrode of the zinc ion battery includes a conductive agent, a binder and the carbon-coated molybdenum-doped vanadium oxide microsphere positive electrode material as described in claim 9.

11. A zinc ion battery, characterized in that: The zinc ion battery comprises the zinc ion battery negative electrode, positive electrode, a separator arranged between the positive and negative electrodes, and an electrolyte as described in claim 10.